Green Foundations - Zainab Y. Alsheikhly; Qusay H. Al-Salami; Ali J. AlAwqati (Cihan University-Erbil Journal of Humanities and Social Sciences)
This research explores the role of educational sustainability in early childhood education (ECE), emphasizing its impact on development and fostering green human capital. Focusing on ages 6–9 in Kurdistan Region schools, it highlights integrating sustainability principles to instil environmental stewardship, social responsibility, and ethical awareness. By examining strategies, curricula, and practices, the research identifies opportunities to empower children as global citizens and green workers while addressing implementation challenges. Combining a literature review with practical examples, it contributes to advancing sustainable education for a more connected and environmentally conscious future. Regression analysis results reveal a significant (Sig.) positive relationship between early childhood environmental education and pro-environmental attitudes and behaviours (PEAB), with a t-value of 6.481 (p≤0.10). The β=0.846 indicates a strong association, and R² = 42.7% of PEAB variance is explained by Early Childhood Environmental Education (ECEE). These findings support H1, confirming ECEE's impact on PEAB in adulthood. While ECEE's influence on Children’s Future Attitudes & Behaviours Toward Sustainability (CFABTS) and GWC is weaker, H3 and H4 are statistically significant. Curriculum development, educator training, and community involvement emerge as key recommendations for achieving the research objectives.